Turbine disc and method of manufacturing the same
Patent Information
- Application Number
- CN202611059866.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]针对现有技术中涡能盘因采用金属材料而必须依赖外部润滑,从而导致油污污染、应用场景受限及维护成本高的技术问题,以及本领域长期存在的“涡能盘高速运转必须依赖润滑油才能保证正常工作”的技术偏见,本发明提供了一种无需润滑、无油污污染、能够适用于高洁净度应用场景的涡能盘及其制备方法
[0017] 1. Achieving high-cleanliness, oil-free operation and expanding application scenarios: This invention replaces traditional metal materials with engineering ceramic materials. Utilizing the extremely low coefficient of friction of engineering ceramic materials (such as zirconia ceramics or silicon nitride ceramics), the vortex energy disk operates at high speeds without the need for any lubricating oil or grease. This fundamentally overcomes the long-standing technical prejudice that high-speed operation of vortex energy disks must rely on external lubrication. This avoids the generation and contamination of oil stains, making the vortex energy disk of this invention suitable for high-cleanliness industries such as food processing, biomedicine, and medical devices, helping to overcome the application limitations of traditional vortex energy disks.
Smart Images

Figure CN122919899A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of vortex energy disk fabrication technology, and in particular to a vortex energy disk and a method for fabricating the vortex energy disk. Background Technology
[0002] Vortex energy disks are core moving components in equipment such as fluid transmission, pneumatic control, and vortex refrigeration, primarily relying on high-speed vortex rotation to achieve energy transfer and conversion. In existing technologies, vortex energy disks are generally made of metal materials such as aluminum alloys and manufactured through traditional processes such as die casting and machining.
[0003] However, these metal-based vortex energy disks have inherent drawbacks. First, metals such as aluminum alloys have a high coefficient of friction, requiring lubrication with oil or grease at high speeds to reduce friction loss and operating noise. Long-term use and adhesion of the lubricating medium inevitably leads to oil residue and penetration inside the equipment, creating a source of contamination. Second, this oil contamination characteristic makes traditional metal vortex energy disks unsuitable for high-standard industries with stringent cleanliness requirements, such as food processing, biomedicine, medical devices, and aseptic purification, significantly limiting their application. Furthermore, lubricating oil deteriorates over time, affecting not only the long-term operational accuracy of the equipment but also increasing the workload and cost of regular oil changes and equipment cleaning.
[0004] For a long time, a technical bias has prevailed among those skilled in the art: that under high-speed operation, the relative speed and contact stress between the friction pairs of a vortex energy disk are extremely high, necessitating externally supplied lubricating oil or grease to establish a stable hydrodynamic lubrication film; otherwise, the vortex energy disk will fail due to severe wear within a short period. Influenced by this bias, the research and improvement efforts of those skilled in the art have long been limited to technical paths centered around "lubrication" itself, such as optimizing lubrication circuit design, improving metal material surface treatment processes, or developing synthetic lubricants. These approaches have remained within the inherent technical framework that "vortex energy disk operation must rely on external lubrication." It is precisely because of this bias that those skilled in the art find it difficult to conceive of fundamentally solving the problems of oil contamination and limited application scenarios by changing the substrate material of the vortex energy disk itself. Summary of the Invention
[0005] In view of the technical problems of existing vortex energy disks, which rely on external lubrication due to the use of metal materials, resulting in oil pollution, limited application scenarios and high maintenance costs, as well as the long-standing technical prejudice in the field that "vortex energy disks must rely on lubricating oil to ensure normal operation at high speeds", this invention provides a vortex energy disk that does not require lubrication, does not cause oil pollution, and is suitable for high-cleanliness application scenarios, as well as its preparation method.
[0006] This invention is proposed based on overcoming the above-mentioned technical biases: by using engineering ceramic materials with low friction coefficients to replace traditional metal materials as the base material of the vortex energy disk, and in conjunction with an integrated injection molding process, the working mode of the vortex energy disk is changed from the material source, thereby completely breaking through the external dependence on lubricating oil.
[0007] To solve the above-mentioned technical problems, the present invention provides a vortex energy disk, including a disk body with vortex grooves formed on the disk body. The vortex energy disk is an integral structure integrally injection molded from engineering ceramic material. The engineering ceramic material has a low coefficient of friction, so that the vortex energy disk can operate normally without the supply of external lubricating medium.
[0008] According to one embodiment of the present invention, the engineering ceramic material is zirconia ceramic or silicon nitride ceramic.
[0009] This invention also provides a method for preparing a vortex energy disk, comprising the following steps: raw material pretreatment: mixing engineering ceramic powder with a binder to prepare a mixture for injection molding; injection molding: injection molding the mixture to obtain an integrally formed vortex energy disk blank; and post-treatment: degumming, sintering, and finishing the vortex energy disk blank to obtain a vortex energy disk made of engineering ceramic material with a low coefficient of friction that can operate under conditions without lubrication medium.
[0010] According to one embodiment of the present invention, the post-processing steps sequentially include: a debinding step, a sintering step, and a finishing step; the debinding step involves heating to 600°C at a rate of 1°C / min in an air atmosphere and holding at that temperature to decompose and remove the binder in the vortex disk blank.
[0011] According to one embodiment of the present invention, the sintering step employs a multi-stage temperature program, the temperature program including: heating to a first preset temperature at a first rate, then heating to a second preset temperature at a second rate, and finally heating to the final sintering temperature at a third rate and holding at that temperature.
[0012] According to one embodiment of the present invention, the first preset temperature is 600°C, the second preset temperature is 1200°C, the first rate is 2°C / min, the second rate is 5°C / min, the third rate is 3°C / min, and the final sintering temperature is 1450°C.
[0013] According to one embodiment of the present invention, after reaching the final sintering temperature and holding it at that temperature, the sintering step further includes controllable cooling to 800°C at a rate of 5°C / min, followed by furnace cooling.
[0014] According to one embodiment of the present invention, in the raw material pretreatment step, the engineering ceramic powder and the binder are mixed at 160°C for 2 hours at a volume ratio of 60:40 to form a uniform injection molding mixture; in the injection molding step, the injection temperature is 190°C, the mold temperature is 60°C, and the injection pressure is 80MPa.
[0015] According to one embodiment of the present invention, the finishing step includes fine grinding and polishing of the workpiece obtained in the sintering step; the fine grinding and polishing includes processing the surface of the workpiece to a surface roughness of Ra 0.05 micrometers to 0.2 micrometers.
[0016] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0017] 1. Achieving high-cleanliness, oil-free operation and expanding application scenarios: This invention replaces traditional metal materials with engineering ceramic materials. Utilizing the extremely low coefficient of friction of engineering ceramic materials (such as zirconia ceramics or silicon nitride ceramics), the vortex energy disk operates at high speeds without the need for any lubricating oil or grease. This fundamentally overcomes the long-standing technical prejudice that high-speed operation of vortex energy disks must rely on external lubrication. This avoids the generation and contamination of oil stains, making the vortex energy disk of this invention suitable for high-cleanliness industries such as food processing, biomedicine, and medical devices, helping to overcome the application limitations of traditional vortex energy disks.
[0018] 2. Improved durability and service life: Compared with traditional aluminum alloy materials, the engineering ceramics used in this invention have higher hardness, excellent wear resistance and superior chemical stability, which can effectively resist wear during high-speed operation and corrosion of fluid media, thereby helping to extend the service life of the vortex energy disk and improve the reliability of the equipment.
[0019] 3. Improved Production Efficiency and Product Precision: This invention employs an integrated injection molding process, enabling the complex vortex grooves, disk body, and assembly holes of the vortex energy disk to be formed in a single step, eliminating the need for subsequent welding or complex secondary machining. This not only simplifies the production process and improves production efficiency but also helps ensure product consistency and dimensional accuracy, facilitating large-scale, high-quality production.
[0020] 4. Reduced maintenance costs: Since no lubricating medium is needed, this invention eliminates the need for regular lubricant replacement and equipment oil cleaning, which helps reduce long-term operation and maintenance costs and improves the stability and reliability of the equipment. Attached Figure Description
[0021] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 This is a photograph of a vortex energy disk according to an embodiment of the present invention.
[0023] Figure 2 This is a schematic flowchart illustrating a method for preparing a vortex energy disk according to an embodiment of the present invention.
[0024] Figure 3 This is a schematic diagram of a temperature program for an optimized sintering process according to an embodiment of the present invention.
[0025] Figure 4 This is a comparison table of friction and wear performance under oil-free operation according to embodiments of the present invention. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. The described embodiments should not be considered as limitations on the invention. All other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this invention. Unless otherwise defined, all technical and scientific terms used in the embodiments of this invention have the same meaning as commonly understood by those skilled in the art. The terminology used in the embodiments of this invention is for the purpose of describing the embodiments of this invention only and is not intended to limit the invention. Before further detailed description of the embodiments of this invention, the nouns and terms involved in the embodiments of this invention are explained, and the nouns and terms involved in the embodiments of this invention are subject to the following interpretations.
[0027] (1) Vortex energy disk: refers to a core moving component used in equipment such as fluid transmission, pneumatic control, and vortex refrigeration. It interacts with the fluid at high speed through one or more vortex grooves formed on the disk body to achieve energy transfer and conversion.
[0028] (2) Engineering ceramic materials: refers to a class of high-performance ceramic materials with excellent mechanical, thermal and chemical properties that can be used as structural components. In this invention, specifically, it may include, but is not limited to, zirconia ceramics or silicon nitride ceramics.
[0029] (3) Integral injection molding: refers to a process in which a mixture containing ceramic powder and organic binder is heated and melted, and then injected into a mold cavity under high pressure to form a complete part containing all complex structural features in one step.
[0030] (4) Vortex disk blank: refers to an intermediate product containing ceramic powder and organic binder obtained through injection molding. Its shape has replicated the structure of the final product, but has not yet undergone post-processing steps such as degumming and sintering.
[0031] (5) Workpiece: In the context of the preparation method, it specifically refers to an intermediate product at different processing stages in the post-processing steps. For example, in the finishing step, it refers to a vortex disk obtained after the sintering step and awaiting fine grinding, polishing or dimensional calibration.
[0032] Please see Figure 1 This invention provides a vortex energy disk, aiming to solve the technical problems of existing aluminum alloy vortex energy disks, which require lubrication, are prone to oil pollution, and have limited application scenarios. The vortex energy disk includes a disk body with vortex grooves. Its core innovation lies in the fact that the vortex energy disk is integrally injection molded from engineering ceramic material. This structural design abandons traditional metal substrates and complex machining processes, changing the material properties and manufacturing paradigm of the vortex energy disk. By using engineering ceramic material with a low coefficient of friction and high hardness, the vortex energy disk can operate at high speeds without external lubrication, thus avoiding dependence on lubricating oil, solving the oil pollution problem, and enabling its application in fields with high cleanliness requirements such as food and medical applications.
[0033] The integrated injection molding process enables the complex vortex structure and disk body to be manufactured in a single step, avoiding stress concentration and precision loss issues associated with traditional multi-part welding or complex machining. This process not only ensures the integrity and consistency of the product structure but also improves production efficiency, laying the foundation for the large-scale application of high-performance ceramic vortex energy disks. By combining specific high-performance materials with advanced molding processes, this solution addresses the inherent defects of aluminum alloy vortex energy disks in the background technology due to material and lubrication dependence, improving product performance and broadening its application range.
[0034] Furthermore, in a preferred embodiment, the engineering ceramic material is either zirconia ceramic or silicon nitride ceramic. These two materials are typical representatives of high-performance engineering ceramics, each possessing unique advantages. Zirconia ceramic, especially tetragonal zirconia (TZP), exhibits high fracture toughness and strength, while also possessing a very low coefficient of friction, demonstrating excellent low friction coefficient and wear resistance, making it a suitable choice for achieving oil-free lubrication operation. Silicon nitride ceramic, on the other hand, is renowned for its superior hardness, excellent thermal shock resistance, and high-temperature strength, making it particularly suitable for harsh operating conditions involving drastic temperature changes or high-temperature fluid environments. By specifying these two materials, this solution provides clear, high-performance material options for different application scenarios, enhancing the relevance and practicality of the technical solution.
[0035] In a preferred embodiment, the vortex energy disk also integrally forms a microchannel network or a groove for mounting sensors. This feature fully leverages the advantage of integral injection molding in manufacturing complex three-dimensional structures. The microchannel network can be designed for circulating coolant, effectively removing the heat generated during high-speed operation of the vortex energy disk and ensuring its dimensional stability and performance reliability under high-temperature conditions; alternatively, these channels can also serve as pathways for sample pretreatment or micro-reactions, giving the vortex energy disk additional functionality. Similarly, the integrally formed sensor groove can precisely accommodate temperature, pressure, or vibration sensors, enabling real-time monitoring of the vortex energy disk's operating status. This integrated design not only simplifies the overall system structure of the device, reducing its size and weight, but also improves the system's integration and reliability, forming the basis for devices with higher integration or monitoring capabilities.
[0036] Please see Figure 2 This invention also provides a method for preparing a vortex energy disk, which closely corresponds to the aforementioned product and aims to provide an efficient and precise process for manufacturing high-performance ceramic vortex energy disks. The method includes the following steps: raw material pretreatment S100, injection molding S200, and post-treatment S300. The raw material pretreatment S100 step aims to transform the ceramic powder into a mixture with good flowability suitable for injection molding; the injection molding S200 step is crucial for achieving the one-time molding of the complex structure of the vortex energy disk; and the post-treatment S300 step is a necessary process for transforming the injection-molded blank into a dense ceramic product with final properties. These three steps are interconnected and together constitute a complete manufacturing chain from powder to high-performance ceramic components.
[0037] Furthermore, such as Figure 2 As shown, the post-processing step S300 sequentially includes: a debinding step S301, a sintering step S302, and a finishing step S303. This sequence is irreversible, and each step undertakes a specific physicochemical transformation task. The purpose of the debinding step S301 is to remove the organic matter, which acts as a temporary binder, from the blank without damaging its structure, forming a green blank with a uniform microporous structure. The sintering step S302 causes the ceramic particles in the green blank to diffuse and recrystallize at high temperature, thereby eliminating internal porosity, achieving densification, and giving the product high strength and high hardness. The final finishing step S303 corrects the dimensional deviations of the workpiece caused by shrinkage after sintering and improves its surface quality to meet the final assembly and use requirements. Through this orderly and meticulous post-processing flow, it is ensured that the final vortex disk meets the design standards in terms of size, performance, and surface quality.
[0038] In a preferred embodiment, the finishing step S303 includes fine grinding and polishing of the workpiece obtained in the sintering step S302. Although the sintered ceramic workpiece already possesses high hardness, its surface is usually relatively rough, failing to meet the application requirements of low friction and low wear. By using superhard abrasives such as diamond for fine grinding and polishing, microscopic protrusions on the surface can be effectively removed, significantly reducing surface roughness. The purpose of this step is to obtain a smooth surface, which is key to achieving a low coefficient of friction in ceramic materials and reducing frictional losses with fluids or other components, thereby contributing to the efficient and stable operation of the vortex disk under oil-free conditions.
[0039] Furthermore, the fine grinding and polishing involves machining the surface of the workpiece to a surface roughness within the range of Ra 0.05 micrometers to 0.2 micrometers. This quantified technical indicator clearly defines the quality standard required for fine machining. Surface roughness is a key parameter affecting friction, wear, sealing performance, and fatigue life. Controlling the surface roughness within this extremely low range creates a near-mirror-like working surface, significantly reducing contact points and frictional resistance at the microscale. This allows the vortex energy disk to form a stable hydrodynamic film or achieve extremely low solid-solid friction during high-speed rotation, which is the core physical basis for the "lubrication-free" operation of the vortex energy disk in this invention. By setting this precise process target, the consistency and reliability of product performance are guaranteed.
[0040] In another preferred embodiment, after the fine grinding and polishing, the finishing step S303 further includes dimensional calibration of the workpiece. Ceramics undergo significant volume shrinkage during sintering, and although shrinkage allowances are reserved in the mold design, the actual shrinkage may still have slight deviations. The fine grinding and polishing process may also affect the final dimensions of the workpiece. Therefore, adding a dimensional calibration step after surface treatment is crucial. This step uses high-precision measuring equipment to detect key dimensions of the workpiece (such as outer diameter, thickness, center hole diameter, etc.) and performs minor adjustments to any out-of-tolerance parts, ensuring that every dimension of the final product meets the tolerance requirements of the design drawings. This helps guarantee its assembly accuracy and dynamic balance performance in the equipment.
[0041] In one optional embodiment, the sintering step S302 employs a multi-stage heating temperature program. For ceramic components with complex structures or large dimensions, rapid heating at a single rate can lead to excessive temperature differences between the inside and outside of the component, generating significant thermal stress and easily causing defects such as cracking and warping. Multi-stage heating allows for different heating rates within different temperature ranges, enabling controlled stress release, removal of residual organic matter, and control of grain growth. This refined heat treatment method is an effective means of solving the technical challenges of ceramic sintering deformation and cracking, and is crucial for improving the yield and dimensional accuracy of complex-shaped vortex disks.
[0042] Further, please refer to Figure 3 The multi-stage heating temperature program includes: heating at a first rate to a first preset temperature T1, then heating at a second rate to a second preset temperature T2, and finally heating at a third rate to the final sintering temperature T3 and holding at that temperature. This programmed heating mode breaks down the entire sintering process into several key stages. The first stage, low-temperature slow heating (to T1), is mainly used to thoroughly remove residual binder and perform pre-sintering; the second stage, faster heating (to T2), can efficiently heat the workpiece to the main sintering zone; the third stage, slow heating (to T3) and holding at that temperature, is key to achieving complete densification. By precisely controlling the temperature and time in this stage, ideal grain structure and material properties can be obtained. Through this synergistic temperature control strategy, precise control of the sintering process is achieved.
[0043] Furthermore, the final sintering temperature is 1450℃. For zirconia ceramics, 1450℃ is a critical sintering temperature. At this temperature, the diffusion kinetics of the ceramic particles are sufficiently active, enabling rapid densification while avoiding abnormal grain growth due to excessively high temperatures, which would degrade mechanical properties. Precisely setting the final sintering temperature T3 to 1450℃ is an optimization result derived from materials science principles and extensive experimental data. It is a key process parameter for achieving good comprehensive properties (such as high density, high strength, and high toughness) in the prepared zirconia vortex disk.
[0044] To better understand the technical solution of the present invention, specific embodiments will be described below. In one specific embodiment, a method for preparing a zirconia vortex disk is provided. First, a raw material pretreatment S100 is performed, selecting high-purity zirconia (3Y-TZP) powder with an average particle size of 0.5 micrometers as the substrate, and mixing it with a paraffin-based binder system (including paraffin, polypropylene, and stearic acid) at a volume ratio of 60:40. The mixture is placed in a mixer and kneaded at a constant temperature of 160°C for 2 hours until a uniform, non-agglomerated feedstock with good flowability is formed.
[0045] Next, the S200 injection molding step is performed. The prepared feedstock is added to a dedicated ceramic injection molding machine, with the barrel injection temperature set to 190°C, the mold temperature to 60°C, and the injection pressure to 80 MPa. The molten feedstock is injected under high pressure into the pre-designed vortex platen mold. The mold cavity structure is as follows... Figure 1 As shown, the disk body and vortex groove can be integrally molded. After a set holding time, cooling is performed, and after the blank has set, the mold is opened and ejected to obtain a structurally complete vortex energy disk blank. At this point, the blank is a composite containing zirconium oxide powder and organic binder, and its geometry is very close to the final product.
[0046] The vortex disk blank then undergoes post-processing S300. This step begins with debinding (S301), where the blank is placed in a temperature-controlled debinding furnace and heated to 600°C at a slow heating rate (e.g., 1°C / min) in air, and held for several hours. This gently and thoroughly decomposes and removes the internal paraffin-based binder, resulting in a porous ceramic blank. Next, a sintering step (S302) is performed, where the debinded blank is transferred to a high-temperature sintering furnace and held at a final sintering temperature of 1450°C (T3) for 2 hours. This completely densifies the ceramic blank, achieving a theoretical density of over 99.5%, forming a high-strength, high-hardness zirconia ceramic structure.
[0047] Finally, the finishing process S303 is performed. A diamond grinding wheel is used to precisely grind the sintered vortex disk workpiece, and the contours within the vortex grooves are trimmed. Then, multiple polishing passes are performed using diamond polishing slurries of different grit sizes until the surface roughness of its main working surfaces reaches Ra 0.2 micrometers. After polishing, precision instruments such as a coordinate measuring machine are used to inspect and calibrate key dimensions of the workpiece, such as the center hole size, outer diameter, and flatness, ensuring that all dimensions are within tolerance. The zirconia vortex disk manufactured in this way is installed in a fluid device and operates directly at high speed without any lubricating oil. Energy conversion is achieved through the efficient interaction between the vortex grooves and the fluid. The effect is that the vortex disk can operate stably for a long time in an oil-free environment, with an extremely low coefficient of friction and almost no wear particles shedding, which helps meet the cleanliness requirements of food-grade and medical-grade equipment. Tests show that its service life is improved compared to aluminum alloy vortex disks of the same specifications.
[0048] In another embodiment, the engineering ceramic material can also be silicon nitride ceramic, which has different performance advantages and is particularly suitable for working conditions with drastic temperature changes. The preparation method of this embodiment is roughly the same in process as the preparation method of the zirconia vortex disk described above, with the main difference being the key process parameters of the raw materials and post-processing. In the raw material pretreatment S100 step, high-purity α-phase silicon nitride (… The powder is mixed with a polyolefin binder to prepare injection molding feed.
[0049] In the injection molding S200 step, the process is similar to that in the aforementioned embodiments, but the injection temperature and pressure are adjusted appropriately according to the rheological characteristics of the silicon nitride feedstock. The biggest difference lies in the sintering step S302 in the post-processing S300. For silicon nitride ceramics, pressure sintering (GPS) is typically used. Specifically, the degummed silicon nitride preform is placed in a pressure sintering furnace and heated to 1750°C and held for 4 hours under a high-purity nitrogen atmosphere of 1.0 MPa. High-pressure nitrogen can effectively suppress the decomposition of silicon nitride at high temperatures, thereby achieving high densification. The subsequent finishing step S303 is the same as the processing method for the zirconia vortex disk. When the manufactured silicon nitride vortex disk is applied to vortex cooling equipment with rapid start-stop or high-temperature fluids, it can withstand temperature cycling impacts from -50°C to 200°C without cracking, maintaining high dimensional stability and a low coefficient of friction, exhibiting good thermal shock resistance.
[0050] Furthermore, to achieve higher dimensional accuracy and reduce product deformation, this invention also provides an optimized post-processing procedure, particularly the sintering step. This optimized process can be applied to the fabrication of the aforementioned zirconia vortex disk. The raw material pretreatment S100 and injection molding S200 steps are exactly the same as in the basic embodiment. The key improvement lies in the sintering step S302 of the post-processing S300, which employs a method such as... Figure 3 This illustrates an optimized multi-stage heating temperature program. The specific program is as follows:
[0051] First, in the heating stage one, the temperature is slowly increased from room temperature to 600℃ (first preset temperature T1) at a first rate of 2℃ / min, and held at this temperature for 1 hour. The purpose of this stage is to ensure that the binder can be slowly and completely discharged, avoiding cracks in the green blank caused by excessive discharge. Next, in the heating stage two, the temperature is rapidly increased from 600℃ to 1200℃ (second preset temperature T2) at a second rate of 5℃ / min for pre-sintering, giving the workpiece a certain strength. Then, in the heating stage three, the temperature is increased from 1200℃ to 1450℃ (final sintering temperature T3) at a third rate of 3℃ / min, entering the main sintering stage, and held at this temperature for 2 hours to achieve complete densification. Finally, in the cooling stage, the temperature is controlled to 800℃ at a rate of 5℃ / min, and then cooled to room temperature in the furnace to avoid cracking of the workpiece due to thermal stress caused by excessively rapid cooling. The vortex energy disk prepared by this optimized sintering process can have its flatness tolerance stably controlled within 0.01 mm and the vortex groove profile dimension deviation less than 0.5%. This optimized sintering process improves the dimensional accuracy and yield of the product.
[0052] The integrated injection molding process employed in this invention is particularly suitable for manufacturing components with complex integrated functions. In one specific application embodiment, this technology was used to design and manufacture the core fluid pump vortex disk for a precision medical dialysis device. This embodiment utilizes the aforementioned zirconia material and optimized fabrication process. Its key innovation lies in the mold design and the integrated structure of the final product.
[0053] More importantly, in designing the mold, in addition to the vortex groove structure on the front of the vortex disk, a complex network of micro-flow channels and multiple standard grooves for mounting sensors were designed on the corresponding positions on its back. Through a single injection molding process, these delicate microstructures are integrally formed with the main body of the vortex disk, requiring no subsequent assembly or processing. In the finishing step S303, in addition to polishing the working surface, for applications requiring extremely high surface quality, such as in ultra-precision optical fluid equipment, the surface roughness can be further reduced to Ra 0.05 micrometers by extending the polishing time or using a finer polishing fluid, thereby obtaining a mirror effect and helping to reduce the coefficient of friction.
[0054] When this vortex energy disk operates in a medical dialysis device, its integrated structure offers the following advantages: The vortex groove structure on the front is responsible for driving the precise delivery of the dialysate; the microchannel network on the back serves as an independent temperature control loop, precisely controlling the temperature of the vortex energy disk through circulating coolant, thereby ensuring the stability of the dialysate temperature; and miniature pressure and temperature sensors are embedded in the pre-set grooves for real-time monitoring of the fluid circuit status. This design realizes a highly integrated, multifunctional core component that not only performs the core function of fluid drive but also integrates temperature control and status monitoring functions, thereby simplifying the overall structure of the medical device, reducing its size, and improving the system's integration and operational reliability. This demonstrates the application of the method of this invention in the manufacture of functionally integrated ceramic components.
[0055] To verify the inventiveness of this invention in material substitution, it is necessary to directly compare the solution of this invention with the closest prior art. Therefore, the following two sets of core performance comparison tests were designed (e.g., Figure 4 (as shown)
[0056] The first group compares friction and wear without oil lubrication. The zirconia injection-molded vortex energy disk of this invention is manufactured without any lubricating medium throughout the entire process, while the existing aluminum alloy vortex energy disk, as a control, is lubricated with lubricating oil according to conventional industrial standards. Both are continuously operated under simulated rated conditions on the same test bench, with a focus on examining the differences in friction coefficient and wear. This group of experiments aims to verify whether the zirconia vortex energy disk, under conditions of completely eliminating external lubrication, still exhibits significantly better wear resistance than the oil-lubricated aluminum alloy vortex energy disk.
[0057] The second group compares start-stop durability and oil-free feasibility. The vortex energy disk of this invention and an aluminum alloy vortex energy disk intentionally left unlubricated were simultaneously subjected to dry-run start-stop cycle tests, directly comparing their survivability under harsh oil-free boundary conditions. This set of experiments aims to reveal the failure mode and rate of failure of the traditional aluminum alloy solution after the removal of lubricating oil protection, thus indirectly proving the excellent anti-adhesion and low friction coefficient load-bearing characteristics inherent in zirconia material itself.
[0058] Both sets of tests point to a core conclusion—the material replacement in this invention is not a simple material change, but a fundamental breakthrough in overcoming the long-standing technical prejudice that "the high-speed operation of the vortex energy disk must rely on external lubrication."
[0059] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A vortex energy disk, comprising a disk body, wherein vortex grooves are formed on the disk body, characterized in that, The vortex energy disk is an integral structure injection molded from engineering ceramic material; the engineering ceramic material has a low coefficient of friction, enabling the vortex energy disk to operate normally without the supply of external lubricating medium.
2. The vortex energy disk according to claim 1, characterized in that, The engineering ceramic material is zirconia ceramic or silicon nitride ceramic.
3. A method for preparing a vortex energy disk, characterized in that, The process includes the following steps: Raw material pretreatment: mixing engineering ceramic powder with a binder to prepare a mixture for injection molding; Injection molding: The mixture is injection molded to obtain an integrally formed vortex energy disk blank; and post-processing: The vortex energy disk blank is degummed, sintered and finished to obtain a vortex energy disk made of engineering ceramic material with a low coefficient of friction that can operate under conditions without lubrication medium.
4. The preparation method according to claim 3, characterized in that, The post-processing steps include, in sequence, a debinding step, a sintering step, and a finishing step; the debinding step involves heating the material to 600°C at a rate of 1°C / min in air and holding it at that temperature to decompose and remove the binder from the vortex disk blank.
5. The preparation method according to claim 4, characterized in that, The sintering step employs a multi-stage temperature program, which includes: heating to a first preset temperature at a first rate, then heating to a second preset temperature at a second rate, and finally heating to the final sintering temperature at a third rate and holding at that temperature.
6. The preparation method according to claim 5, characterized in that, The first preset temperature is 600℃, the second preset temperature is 1200℃, the first rate is 2℃ / min, the second rate is 5℃ / min, the third rate is 3℃ / min, and the final sintering temperature is 1450℃.
7. The preparation method according to claim 5, characterized in that, After reaching the final sintering temperature and holding it at that temperature, the sintering step also includes controlled cooling to 800°C at a rate of 5°C / min, followed by furnace cooling.
8. The preparation method according to claim 3, characterized in that, In the raw material pretreatment step, the engineering ceramic powder and the binder are mixed at 160°C for 2 hours at a volume ratio of 60:40 to form a uniform injection molding mixture; in the injection molding step, the injection temperature is 190°C, the mold temperature is 60°C, and the injection pressure is 80MPa.
9. The preparation method according to claim 4, characterized in that, The finishing step includes fine grinding and polishing the workpiece obtained in the sintering step; the fine grinding and polishing includes processing the surface of the workpiece to a surface roughness of Ra 0.05 micrometers to 0.2 micrometers.
10. The preparation method according to claim 3, characterized in that, The engineering ceramic material is zirconia ceramic or silicon nitride ceramic; when the engineering ceramic material is silicon nitride, the sintering step adopts a gas pressure sintering process, which involves heating to 1750°C and holding at that temperature for 4 hours under a nitrogen protective atmosphere of 1.0 MPa.